The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1098/rsfs.2011.0090
|View full text |Cite
|
Sign up to set email alerts
|

Models in animal collective decision-making: information uncertainty and conflicting preferences

Abstract: Collective decision-making plays a central part in the lives of many social animals. Two important factors that influence collective decision-making are information uncertainty and conflicting preferences. Here, I bring together, and briefly review, basic models relating to animal collective decision-making in situations with information uncertainty and in situations with conflicting preferences between group members. The intention is to give an overview about the different types of modelling approaches that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 81 publications
(258 reference statements)
4
91
0
Order By: Relevance
“…In particular, the author considers the situation where the collective decision of social animals within a group involves elements of conflict: the ultimate decision can clash with the preferred decision of some individuals. Recently, the same author showed that conflicting interests of individuals eventually make the collective decision more accurate [18], and this paper addresses the generality of this finding. By constructing a fairly simple model and computing the probabilities of group decisions, the author concludes that for animals without personal preferences, the probability of making a correct collective decision is higher.…”
mentioning
confidence: 82%
“…In particular, the author considers the situation where the collective decision of social animals within a group involves elements of conflict: the ultimate decision can clash with the preferred decision of some individuals. Recently, the same author showed that conflicting interests of individuals eventually make the collective decision more accurate [18], and this paper addresses the generality of this finding. By constructing a fairly simple model and computing the probabilities of group decisions, the author concludes that for animals without personal preferences, the probability of making a correct collective decision is higher.…”
mentioning
confidence: 82%
“…Groups often face a trade-off between decision accuracy and speed, but appropriate fine-tuning of behavioural parameters could achieve high accuracy while maintaining reasonable speed. The right balance of interdependence and independence between animals is crucial for maintaining group cohesion and achieving high decision accuracy [78]. Cai developed artificial fish school swarm algorithm applied in a combinatorial optimization problem to minimize the turnaround time of vessels at container terminals so as to improve operation efficiency customer satisfaction [79].…”
Section: Fish Schoolingmentioning
confidence: 99%
“…The right balance of interdependence and independence between animals is crucial for maintaining group cohesion and achieving high decision accuracy [78] FSm…”
Section: Knowledge and Requirement Matchingmentioning
confidence: 99%
“…In a thoroughly comprehensive overview of the topic, Conradt [19] considers how collective group decisions are made in the context of two key scenarios: (i) where information available to individuals in the group is uncertain and (ii) where individuals in the group have conflicting preferences. In the case of information uncertainty, Conradt [19] first details quorum responses, where the decision at the individual level is influenced by how many others in the group have made a certain decision. She then discusses the effective leadership model, where a small sub-set of the group that are 'informed' about the correct movement direction can lead a group of uninformed individuals effectively.…”
Section: Advances In Behavioural Ecology Theorymentioning
confidence: 99%